IN THE SWEET BULGARIAN PEPPER, WHICH IS GROWN IN THE CONDITIONS OF KIDROPONICS, IT IS USED TO MAKE A DECOCTION OF GREENHOUSE WATERCRESS (TRIALEURODES VAPORARIORUM WEST.) DYNAMICS OF DEVELOPMENT (British Journal of Global Ecology and Sustainable Development, 2022)
The article provides information on the spread of greenhouse spills worldwide, causing damage to the exported sweet Bulgarian pepper grown in modern kidroponics lighthouses, the harm that causes vegetable and potato crops in different development phases. Also, studies on the dynamics of the development of the flow of sweet Bulgarian pepper in the greenhouse were carried out on 2.4 hectares of the “Daromad Fayz Omad” greenhouse farm in the Samarkand region of the Samarkand region. Based on the research carried out, practical conclusion and recommendations were made.